A molecular marker linked to the male gender of Actinidia arguta Siebold & Zucci - Liu, X.Z.; Lv, T.W.; Liu, H.M.; Zhang, H.Y. (The Indian Journal of Genetics and Plant Breeding, 2016)
To distinguish the female plants in early stage, BSA and RAMP techniques were employed to screen and characterize molecular markers linked to hardy kiwi gender. One RAMP marker GA(CT)4/S129450, was found to be tightly linked to the male gender. Then the RAMP maker was cloned, sequenced, and conversed into SCAR marker. And early stage selection was carried out using the SCAR marker on 142 F1 progeny from crossing between Yongshan 11 and Yongshan 5. It is the first report on distinguishing the gender of hardy kiwi in early stage.